The Impact of Artificial Intelligence on Modern Program Management - Gaurav Gupta, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of Artificial Intelligence (AI) in program management represents a transformative shift in how organizations approach project planning, execution, and monitoring. This comprehensive article examines the multifaceted impact of AI technologies across various aspects of program management, including project planning, risk management, process automation, team collaboration, and strategic decision-making. Through analysis of recent research and industry implementations, it explores how AI-powered solutions enhance decision-making processes, improve risk identification and mitigation strategies, and optimize resource allocation. The article demonstrates that AI systems effectively process vast amounts of project data to generate actionable insights, enabling more informed decision-making and proactive project management approaches. Furthermore, the article investigates how AI facilitates team collaboration through advanced communication analysis and automated workflow optimization. It indicate that while AI significantly augments project management capabilities through automation and advanced analytics, human judgment remains crucial for strategic decision-making and complex problem-solving. The article concludes by examining future implications and emerging trends in AI-driven project management, highlighting the importance of balanced integration between technological capabilities and human expertise.
Keywords: Artificial Intelligence in Project Management; Predictive Analytics; Process Automation; Team Collaboration; Strategic Decision Support